EFFECT OF EDUCATION, TRAINING, EXPERIENCE, INDEPENDENCE AND PROFESSIONAL ATTITUDE ON THE EFFECTIVENESS OF INTERNAL AUDIT - ALFRIN ERNEST MARTEN USMANY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This study aims to analyze the effect of education, training, experience, independence and professional attitude on the effectiveness of internal audit. The object of this research is the inspectorate auditor of the Maluku Provincial Government and the Ambon City Government inspectorate auditor. Questionnaires were distributed as many as 100 research samples, 47 questionnaires were returned. Data were analyzed using Partial Least Square (PLS) with the help of SmartPLS software version 3.0. The endogenous variables in this study are the effectiveness of internal audit while the exogenous variables are education, training, experience, independence and professional attitude. The results of this study indicate that the variables of experience, independence and professional attitude have a significant positive effect on the effectiveness of internal audit. Meanwhile, education and training variables have no significant effect on the effectiveness of internal audit.